How do environmental changes challenge the sustainable development of Asia? - AI-Amin, Abul Quasem (Academic Journals Inc., 2015)
This study raised the sustainable development issues in Asian developing countries following the broad three dimensions of the challenges on firstly-economic, secondly-social and thirdly-environmental subjects. To have a good understanding of the sustainable development, a delivery of possible scope and action of strategies is communicated in this article for the coherent and efficient progress of sustainable development agenda. In addition, how a possible action such as (1) Equity, (2) Justice, (3) Good governance (public investments in health, nutrition, family planning and education) and (4) Fair-aspiration (socio-political reforms to align with social objectives) are also raised with an operational argument. This study layout why a business-as-usual typical policy and effort is not an appropriate selection as an action to overcome the existing challenges and why fourfold visionised option is essential to rethink to transform a change for the remaining critical issues at the local and national level in Asian developing countries and other developing countries alike